Mexico : Financial Sector Assessment Program Update; Technical Note; Industrial Organization and Competition; Pension System in Mexico. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
The technical note on Mexico's Financial Sector Assessment Program update analyzes that the private pension system's regulator in Mexico has introduced innovate rules. Mexico, as with many other countries in Latin America, has adopted an individual capitalization pension system. The design of these pension reforms confers the administration of pension funds to private companies. Under these schemes, competition plays a key role, keeping prices low, a good quality of service, and an efficient investment allocation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet